Freond ic gemete wið : Perspectives on Medieval Britain ; Language, Literature, Society. - Hejná, Michaela (Cambridge Scholars Publishing, 2013)
Freond ic gemete wið: Perspectives on Medieval Britain; Language, Literature, Society is the outcome of a symposium convened at Charles University in Prague in March 2012. It offers a mosaic of perspectives on medieval Britain represented by detailed and closely focused analyses of individual aspects of linguistic, literary and socio-cultural practice from the early Anglo-Saxon period to the late Middle Ages. The contributions in the field of linguistics are concerned with the problematics ...